EFFECTIVE TECHNIQUES FOR CREATING AN EMOTIONALLY POSITIVE ATMOSPHERE OF TEACHING FOREIGN LANGUAGES - Kushakov, Yusup (Журнал иностранных языков и лингвистики, 2023)
In this article, creating emotionally good atmosphere of teaching foreign languages is considered as the problems of the modern methods as a whole. According to the author, teaching foreign languages pursues a comprehensive implementation of practical, educational, educational and developmental goals. Creating relevant atmosphere promotes in reaching these goals. The author indicates the key factors in these sphere.